On the indentation of a poroelastic halfspace. (April 2020) - Selvadurai, A.P.S.; Samea, P.
Abstract: This paper re-examines the problem of the indentation of a halfspace region with Biot poroelastic properties by considering the displacement and pore fluid pressure boundary conditions that are consistent for adhesive contact at an impermeable interface. The mixed initial boundary value problems associated with the adhesive-impermeable indentation are reduced to a set of coupled Fredholm integral equations of the second-kind in the Laplace transform domain. These equations are solved to establish the time-dependant indentation response of the indenter. The results are supplemented by sets of bounds obtained by maintaining a zero radial displacement condition within the contact zone and either zero pore fluid pressure boundary conditions or impermeable conditions on the entire surface of the halfspace or impermeable conditions within the contact region but free-draining exterior to the indenter. The accuracy of the numerical schemes used in the solution of these poroelastic contact problems is also discussed.